2011
DOI: 10.1111/j.2042-7158.2011.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of P-glycoprotein reduces intracellular accumulation of beta amyloid: investigation of P-glycoprotein as a novel therapeutic target for Alzheimer's disease

Abstract: Objectives Several studies have suggested the efflux transporter P-glycoprotein (P-gp) to play a role in the etiology of Alzheimer's disease through the clearance of amyloid beta (Aβ) from the brain. In this study, we aimed to investigate the possibility of P-gp as a potential therapeutic target for Alzheimer's disease by examining the impact of P-gp up-regulation on the clearance of Aβ, a neuropathological hallmark of Alzheimer's disease. Methods Uptake studies for 125I-radiolabelled Aβ1–40, and fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 35 publications
4
58
0
Order By: Relevance
“…P-gp is expressed abundantly on the canalicular side of hepatocytes, and Ab 40 is a P-gp substrate (Lam et al, 2001). P-gp at the apical side of BBB has been shown to play a substantial role in controlling Ab levels in the brain by enhancing its removal from brain to blood and by limiting Ab access to the brain (Cirrito et al, 2005;Kuhnke et al, 2007;Abuznait et al, 2011). To study the role of P-gp in the canalicular excretion of Ab 40 , two potent P-gp inhibitors, verapamil and valspodar, were used.…”
Section: Discussionmentioning
confidence: 99%
“…P-gp is expressed abundantly on the canalicular side of hepatocytes, and Ab 40 is a P-gp substrate (Lam et al, 2001). P-gp at the apical side of BBB has been shown to play a substantial role in controlling Ab levels in the brain by enhancing its removal from brain to blood and by limiting Ab access to the brain (Cirrito et al, 2005;Kuhnke et al, 2007;Abuznait et al, 2011). To study the role of P-gp in the canalicular excretion of Ab 40 , two potent P-gp inhibitors, verapamil and valspodar, were used.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro accumulation studies using the human colon adenocarcinoma cell line LS-180, which endogenously expresses ABCB1 and pregnane-X-receptor (PXR), 67 demonstrated that the cotreatment of Aβ 40 with the ABCB1 inhibitor verapamil significantly increased Aβ 40 cellular accumulation, confirming its role in limiting Aβ cellular entry. 38 Moreover, utilizing in vivo brain efflux index (BEI%) studies conducted on C57BL/6 mice provided further evidence to the important role of ABCB1 in the clearance of 125 I-Aβ 40 from the brain where inhibition studies with valspodar (ABCB1 inhibitor) caused 18% reduction in 125 I-Aβ 40 clearance (P < 0.05).…”
mentioning
confidence: 99%
“…68 In addition, in vitro and in vivo up-regulation of ABCB1 by different ABCB1 inducers significantly modulated Aβ levels. 38,65 The in vitro treatment of LS-180 cells with rifampicin, caffeine, verapamil, hyperforin, and β-estradiol, and to a lesser extent pentylenetetrazole and dexamethasone, resulted in significant decrease in the intracellular accumulation of Aβ 40 when compared to control as a result of ABCB1 up-regulation. 38 Furthermore, in vivo BEI% studies conducted on C57BL/6 mice treated with rifampicin or caffeine significantly enhanced Aβ 40 clearance by more than 20% when compared to control vehicle treated mice.…”
mentioning
confidence: 99%
“…mediated) in the cell membranes with transport of cholesterol to HDL and LDL [138] [139]. In AD, upregulation of Pgp is involved in the rapid clearance of amyloid beta from the brain with implications for Pgp as a therapeutic target for amyloid beta and xenobiotic clearance in the brain [143] [144]. Upregulation of Pgp activity in the liver is involved in PXR protein levels with implications of diet on PPAR-Sirt1/PXR interactions [145] [146] involved in regulation of Pgp mediated xenobiotic clearance in chronic diseases such as the kidney.…”
Section: Endocrine Disruptors As Risk Factors For Obesity and Chronicmentioning
confidence: 99%